The Influence of Educaplay Media Usage on Learning Outcomes in the Arts and Culture Subject of 8th Grade Students at MTs Negeri 2 Sidrap - Muh.Farhan Jufri; Syamsunir Syamsunir; Abd. Kahar; Hasanuddin Hasanuddin (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effect of using the interactive learning media Educaplay on the learning outcomes in the Cultural Arts subject of eighth-grade students at MTs Negeri 2 Sidrap. The background of the research is based on the low interest and achievement of students in Cultural Arts due to the use of conventional teaching methods that lack engagement. This research employs a quantitative approach with a quasi-experimental design using a posttest-only control group design. The sample consists of two classes: class VIII B as the experimental group using Educaplay, and class VIII A as the control group using conventional learning methods. The research instrument was a multiple-choice test consisting of 30 questions. Data were analyzed using the mean calculation technique. The results show that the average score of students in the experimental group was 84.37, which is significantly higher than the control group’s score of 53.91. These findings indicate that the use of Educaplay positively and significantly affects student learning outcomes in the Cultural Arts subject. Therefore, Educaplay can be considered an effective alternative to enhance the quality and engagement of the learning process.